Fly Trap From Waste: The Effectivity trap based Plastic Blue Bottle - Daramusseng, Andi; Hadiyanto, Muhammad Hadiyanto; Ikhwanuttaqwa, Muhammad Alif Naufan; Ridwan, Muhammad Rahul; Alfiansyah, Muhammad; Yuliani, Ni Luh Nisa (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Some species of flies act as vectors of infectious diseases mainly infectious diseases of the gastrointestinal tract. Flies can not be completely eradicated but the number can be suppressed to an extent that is not harmful. One way to reduce the number of flies in the environment is by the use of flytraps. The study aims to test the effectiveness of bait variations on the flytrap of blue plastic bottle waste against the number of trapped flies. This research is a quasi-experiment with a posttest-only control design. Measurement of bait variations on the flytrap of blue plastic bottle waste with a flytrap under the chicken coop with a distance between the flytrap of 1 meter. Installing flytrap from 09.00 WITA until 13.00 WITA for 5 days in the same way. The results showed that the number of flies trapped in each flytrap is different. Flytrap with fish gill bait is most effective in attracting flies to be trapped as many as 281 flies and baits that are less favored by flies that are rotten tempeh bait as many as 6 flies for 5 days. Kruskal Wallis test showed that there was a difference in flies trapped in the plastic waste flytrap with variations of fish gill bait, chicken innards, shrimp paste, and rotten tempeh with a p-value of 0.022 < 0.05. This study recommends the use of fish gills in controlling flies both in the home and market environment.